Studi Laboratorium Siklus Hidup Anopheles vagus Pradewasa sebagai Vektor Filariasis dan Malaria di Provinsi Nusa Tenggara Timur - Varry Lobo; Hanani Melangwala Laumalay (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2019)
Anopheles vagus is one of the vectors that plays an essential role in malaria infection in East Nusa Tenggara, Indonesia. This vector’s density is related to population dynamics and the environment. The high population density is fluctuated according to the birth and death rate of the mosquitos on their life cycle. This is an observational study that employed a cross-sectional design aimed to identify the life cycle of pre-adult An. vagus mosquitos. The sample was collected from Manggarai Barat and Kupang regions. Sample was taken from around cattle’s cages between 6.00pm-12.00am and were the ones that have sucked cattle’s blood. Identification and colonization were conducted in Loka Litbangkes Waikabubak Laboratory. Data was collected through an hourly observation form and then analyzed descriptively. The results indicated that an adult An.vagus could produce 42-184 eggs each time it laid eggs with 79% hatching rate succeed. The life cycle of an An.vagus under a controlled environment in the laboratory was as following phases: egg (1-4 days), larvae (9-19 days), pupa (1-8 days). Anopheles vagus needed an average of 57.2 minutes to mate and 13 hours to suck blood after the mating process. The highest death rate (28.05%) occurred in instar IVof larvae stage. Pre-adult of An. vagus needed 11-31 days in with the environment that conditioned at 21.1°C and 74.3% humidity for their development,while the highest death rate observed at instar IV.